Implementasi Lean Manufaturing Pada Produksi Machining Cast Wheel Dengan Menggunakan Metode WAM dan VALSAT - Daonil Daonil; T. Yuri M. Zagloel (Journal of Industrial and Engineering System, 2021)
The purpose of this research is to eliminate waste in machining cast wheel line production using lean manufacturing implementation. This research use lean manufacturing method with Waste Assessment Model (WAM) for identification waste of manufacturing process and Value Stream Analysis Tools (VALSAT) to choose mapping tools which will be used in waste analysis. Based on the analysis result, there are three recommendations. The recommendations are modification design soft jaw on machine OP 20 (facing and boring), application sampling method for OP 40 (leak test), and unification OP 70/OP 60 (washing). The result of evaluation recommendations shows performance improvement in machining cast wheel line production, there are increase in production capacity by 1,350 sets per day, decrease in reject rate by 2%, and efficiency of man power by reduce 3 peoples.